Midazolam alters acid-base status less than azaperone during the capture and transport of southern white rhinoceroses (Ceratotherium simum simum) - Pohlin F; Buss P; Hooijberg EH; Meyer LCR (MDPI (Basel, Switzerland), 2020)
Acidemia represents a major life-threatening factor during rhinoceros capture. The acid-base status during rhinoceros transport is unknown. The purpose of this study was to describe changes in acid-base status during rhinoceros capture and transport and compare these changes between rhinoceroses sedated with azaperone or midazolam. Twenty-three wild white rhinoceros bulls were road-transported 280 km for reasons unrelated to this study. Rhinoceroses were captured with etorphine-azaperone (Group A) or etorphine-midazolam (Group M). During transport, azaperone (Group A) or midazolam (Group M) was re-administered every 2 h and venous blood collected. Changes in blood pH and associated variables were compared over time and between groups using a general linear mixed model. Rhinoceroses of both groups experienced a respiratory and metabolic acidosis during capture (pH 7.109 ± 0.099 and 7.196 ± 0.111 for Group A and Group M, respectively) that was quickly compensated for by the start of transport (pH 7.441 ± 0.035 and 7.430 ± 0.057) and remained stable throughout the journey. Rhinoceroses from Group M showed a smaller decrease in pH and associated variables at capture than rhinoceroses from Group A (p = 0.012). The use of midazolam instead of azaperone could therefore improve the success of rhinoceros capture and thus, contribute to the outcome of important conservation translocations.
Keywords: acidosis; azaperone; midazolam; rhinoceros; translocation; Henderson-Hasselbalch; Stewart’s approach; wildlife